RETRACTION Putro, B. N., Nurkadri, N., Sahabuddin, S., Laksana, A. A. N. P., Setyawan, H., HB, G., Harmanto, H., Darmawan, A., Tafuri, F., & Latino, F. (2024). Logro de los resultados del aprendizaje de la educación física de los estudiantes de último curso de secundaria en función del sexo y la frecuencia de estudio (Examining physical education learning outcomes of senior high school students: the impact of gender and learning frequency). Retos, 60, 393–404. https://doi.org/10.47197/retos.v60.109042 - RETOS, RETOS (Retos, 2025)
Putro, B. N., Nurkadri, N., Sahabuddin, S., Laksana, A. A. N. P., Setyawan, H., HB, G., Harmanto, H., Darmawan, A., Tafuri, F., & Latino, F. (2024).  Logro de los resultados del aprendizaje de la educación física de los estudiantes de último curso de secundaria en función del sexo y la frecuencia de estudio (Examining physical education learning outcomes of senior high school students: the impact of gender and learning frequency). Retos, 60, 393–404. https://doi.org/10.47197/retos.v60.109042Retraction of the article by the editor of the journal. There has been several clear and conclusive proofs that the authorship of the article has been manipulated. The accepted Word document was sent with the names of the authors that appeared in the “Corrections for the edition” message so that they could only make the orthographical corrections that were needed. The corresponding author (or whoever hurt him) changed the authors of the aforementioned Word document that was sent to them, returning a document together with these corrections made with new authors, all without any express notification, without any document explaining the changes made accepted by all the authors and, of course, without express authorization from the journal Retos between both moments. Likewise, a large number of citations and references were manipulated. With this fraudulent document the galleys were made and the article was definitively published, assigning it the corresponding DOI.Authors in the Word document of the article submitted for review: 9Authors in the published PDF with modified authors: 10Differences between the authors between both moments: +5 y -4 (Additions: Nurkadri, Sahabuddin, Anak Agung Ngurah Putra Laksana, Harmanto, Arief Darmawan. Eliminated: Arief Darmawan, Zulbahri Zulbahri, Özgür Eken, Ratko Pavlovic)